Enhancing the implementation effectiveness of the "Double reduction" policy from a social-psychological perspective: Optimization of basic education policy implementation pathways and construction of evaluation mechanisms - Yuanli Qi; Aida Hanim A. Hamid; Mohamed Yusoff Mohd Nor (Environment and Social Psychology, 2025)
The "Double Reduction" policy represents a major reform initiative in basic education. Its effective implementation faces complex social-psychological challenges. This study adopts a social-psychological perspective. We employ mixed research methods. The research examines the psychological mechanisms and optimization paths of policy implementation through questionnaire surveys (N=1847) and in-depth interviews (N=156).The findings reveal several key patterns. Policy implementation resistance stems from three levels: cognition, emotion, and behavior. The cognitive bias rate reaches 68.7%. Emotional anxiety intensity stands at 73.3%. Behavioral deviation rate measures 73.5%. These three factors interact to form a chain of implementation barriers. Social support system intervention experiments show important results. Emotional support demonstrates the highest efficacy at 4.5 points. Comprehensive intervention increases policy compliance from 61.8% to 89.3%. This represents a 44.5% improvement. Systematic intervention combining cognitive restructuring, emotional guidance, and behavioral correction produces measurable outcomes after 8 weeks. Cognitive accuracy reaches 87.6%. Negative emotional intensity decreases by 46.5%. Behavioral compliance improves by 47.2%.The research constructs a five-dimensional assessment model. This model is based on psychological well-being, satisfaction perception, behavioral intention, social support, and value identification. The Cronbach α ranges from 0.83 to 0.89. Analysis reveals that student participation shows the largest gap at 37.1%. Role clarity scores lowest at 45.8%.This study provides empirical evidence for psychological mechanism research in educational policy implementation. It offers theoretical guidance and practical pathways for optimizing the "Double Reduction" policy and constructing evaluation mechanisms.